2016
DOI: 10.1080/00224545.2016.1140118
|View full text |Cite
|
Sign up to set email alerts
|

Wrongness in different relationships: Relational context effects on moral judgment

Abstract: Morality primarily serves socio-relational functions. However, little research in moral psychology investigates how relational factors impact moral judgment, and a theoretically grounded approach to investigating relational context effects on moral judgment is lacking.We used Relationship Regulation Theory (Rai & Fiske, 2011) and Moral Foundations Theory (Graham et al., 2011) to explore how varying the relationship between actors and victims impacts judgment of different types of moral violations. Across three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 26 publications
7
54
0
Order By: Relevance
“…A number of researchers have begun to investigate how social contexts may influence moral judgment, whether those social contexts are grounded in groups (Carnes et al, 2015;Ellemers & van den Bos, 2009) or relationships (Fiske & Rai, 2014;Simpson et al, 2016), and the present study fits within this bourgeoning body of research. In the present studies we found that the intergroup nature of war influenced people's moral judgments about harm in war -even if they belonged to neither of the two groups actually at war -and that the usually robust difference between switch and footbridge scenarios was attenuated in the war context.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A number of researchers have begun to investigate how social contexts may influence moral judgment, whether those social contexts are grounded in groups (Carnes et al, 2015;Ellemers & van den Bos, 2009) or relationships (Fiske & Rai, 2014;Simpson et al, 2016), and the present study fits within this bourgeoning body of research. In the present studies we found that the intergroup nature of war influenced people's moral judgments about harm in war -even if they belonged to neither of the two groups actually at war -and that the usually robust difference between switch and footbridge scenarios was attenuated in the war context.…”
Section: Discussionsupporting
confidence: 52%
“…We know that social and relational context influences moral judgments. For example, care and loyalty are seen as more relevant moral concerns among intimates (e.g., members of a family, a group of close friends) than among members of a task group (e.g., members of a jury, the cast of a play), even if the person making the judgment is positioned outside of these groups (Carnes, et al, 2015;Simpson & Laham 2015;Simpson, Laham, & Fiske, 2016). War is a social context involving unique relationships: Hierarchical relationships among members of the armed forces, horizontal relationships between soldiers of the same unit, relationships across the military-civilian divide, and the antagonistic relationship between the warring parties.…”
mentioning
confidence: 99%
“…Context should also be considered. In one of the latest study, Simpson, Laham and Fiske (Simpson, Laham, & Fiske, 2016) changed the actors of the moral violations and they found that in the context of studentprofessor relation purity violations are more likely to be perceived as morally wrong compared to the context of siblings.…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…Specifically, respondents were randomly assigned to the role of provider or user and read hypothetical descriptions of the three business models, after which they chose one platform on which to share and were asked to score each platform on CS, EM, and MP. By comparison to separate evaluation design, a joint evaluation design provides respondents with a shared context for comparison (McGraw & Tetlock, 2005 showed that evaluations of relational construal were similar to the ones obtained from designs in which respondents only read one scenario (Simpson et al, 2016).…”
Section: Respondents and Proceduresmentioning
confidence: 77%
“…On this platform, people feel that they belong to the same group and have a lot in common with one another.” Next, respondents were asked to think about each of the three sharing platforms in turn and to rate to what extent the descriptions matched how they expected people to interact on this platform on a 7‐point Likert scale (1 = not at all; 7 = to a great extent). This approach is similar to the one described in Biber, Hupfeld, and Meier () and Simpson et al () and allows to capture in a short amount of time respondents’ perceptions of peer‐to‐peer relationships for each of the business models.…”
Section: Methodsmentioning
confidence: 99%